PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA PERUSAHAAN MANUFAKTUR SUBSEKTOR KERAMIK PORSELEN DAN KACA PERIODE 2022-2024 - Shafa Kamila Hamzah Hamzah; Putri Khoerunnisa; Reymond Filar Ramadhan; Yuana Rizky Octaviani Mandagie (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2025)
This study analyzes the effect of liquidity and solvency on the financial performance of manufacturing companies in the ceramics, porcelain, and glass sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. It uses a sample of 7 companies, with data processed using multiple linear regression analysis. The results show that liquidity has a significant effect on financial performance, while solvency does not. These findings suggest that the ability to meet short-term obligations is given more attention by investors than capital structure.